Risk Assessment for Managing Risks in Infrastructure Projects - Srinivas, K. (Prabandhan: Indian Journal of Management, 2015)
Construction projects are prone to complexity and uncertainty. Management of risks is a deciding factor in success or failure of the projects. Each construction project in itself is unique and very few similarities exist between any two projects, even if the construction is in the same sector. Every construction project has its own share of risks, and the risks will not be the same even if a similar project is executed in two different places with different terrain and topography. Risk management involves identifying risks, assessing them, and developing suitable strategies to manage them. An attempt has been made in the present study to analyze the risk scenario in the construction industry by meeting stakeholders and eliciting information from them for recognizing the risk factors that influenced the success of two projects - one thermal and one hydel project under construction in the state of Andhra Pradesh. Risks can be assessed qualitatively and quantitatively. This paper reviewed the various techniques used for quantifying risks and focused on evaluating the risks using the Risk factor and Priority model. The evaluation of risks will be an effective tool for prioritizing the risks for successful completion of the projects.